2009
DOI: 10.1177/1354856509342341
|View full text |Cite
|
Sign up to set email alerts
|

The De/Stabilization of Identity in Online Fan Communities

Abstract: This article explores the negotiation of fan identity within two internet-based fan communities (the television fan site City of Angel and videogame fan site Silent Hill Heaven) in responses to two destabilizing events (the ‘Save Angel’ campaign and the release of the Silent Hill film). The article explores three aspects of the posting activity relating to these events: the ways that members, at times, constitute what it is to be a fan through the reification of their own agency; the ways that posters conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Positive associations between geek culture engagement and fantasy proneness, crystallized and fluid intelligence, need for cognition, and sensation seeking would be consistent with the need for engagement hypothesis. Because many fan groups distinguish themselves as having more active engagement with their media (e.g., [ 10 ]), we predicted geeks would be individuals who had higher need for intellectual (e.g., need for cognition) and emotional (e.g., sensation seeking) stimulation.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Positive associations between geek culture engagement and fantasy proneness, crystallized and fluid intelligence, need for cognition, and sensation seeking would be consistent with the need for engagement hypothesis. Because many fan groups distinguish themselves as having more active engagement with their media (e.g., [ 10 ]), we predicted geeks would be individuals who had higher need for intellectual (e.g., need for cognition) and emotional (e.g., sensation seeking) stimulation.…”
Section: Studymentioning
confidence: 99%
“…Mizer calls the latter activity the “ironic imagination” and describes it as particularly dependent on social interaction, as getting multiple people to treat a fantasy universe as real can extend the escapism beyond the original work of fiction. Consistent with this view, fandom members (who fit the definition of a geek) have been shown to distinguish themselves from more passive media consumers through their agency in shaping media [ 10 ], their ability to handle extreme or taboo content [ 11 ], and their active intellectual engagement [ 1 , 11 ] with media, at times referring to non-geeks as less intelligent or aware [ 1 , 11 ]. Therefore, geek culture may be distinguished by the tendency to actively participate in one’s own escapism and entertainment, especially in tandem with other people.…”
Section: Introductionmentioning
confidence: 99%
“…It seems identity resolution can be assisted if it can involve others through dialogue (Hermans & Hermans-Jansen, 1995). There is a dearth of research into the identity resolution by teachers of their views on social media use Helpful in thinking about this is research which links identity to online interaction (Herring, 2003;Jones, 2005;Page, 2012;Thurlow et al, 2004;Whiteman, 2009), exploring how identity is revealed through discourse. Such identity work takes place both off and online (Jones, 2005;Thurlow et al, 2004) and identities can overlap (Herring, 2003).…”
Section: The Psychological Notion Of I-positionsmentioning
confidence: 99%
“…Some of this literature concerns cult television series such as The X-Files (Scodari, 2003) and Buffy The Vampire Slayer (Johnson, 2007) and takes the form of attacks on disliked characters, unfavorable production decisions, perceived below-strength scriptwriting, and rival Downloaded by [Universiteit Leiden / LUMC] at 03:03 21 November 2014 GILES fans with inappropriate preoccupations. Other studies have reported factions developing among fans of games, such as Silent Hill (Whiteman, 2009), Fallout (Milner, 2011), and Mass Effect (Dutton, Consalvo, & Harper, 2011). In all these studies, criticism serves partly to establish hierarchies among fans, at the top of which "alpha fans" (Dutton et al, 2011) assume the power both to influence production decisions and shape the responses of other fans.…”
Section: The Changing Nature Of Fandommentioning
confidence: 93%